United Kingdom immune thrombocytopenia registry: retrospective evaluation of bone marrow fibrosis in adult patients with primary immune thrombocytopenia and correlation with clinical findings. (5th March 2015) - Rizvi, Hasan; Butler, Tom; Calaminici, Mariarita; Doobaree, Indraraj U.; Nandigam, Raghava C.; Bennett, Dimitri; Provan, Drew; Newland, Adrian C.
Summary: Fibrosis has been reported in some patients with immune thrombocytopenia (ITP) treated with thrombopoietin receptor agonists (TPO‐RA). However, fibrosis has also been reported in patients with various stages of ITP, who were TPO‐RA treatment‐naïve. In our study, we looked for fibrosis in bone marrow trephine biopsies taken at initial diagnosis from 32 adult patients with ITP. Ten of the 32 evaluated samples (31·25%) showed increased reticulin (Grade 1–2 on Bauermeister scale and Grade 0–1 on the European Consensus scale), which showed a positive correlation with ethnicity (0·3%) but did not correlate with disease severity, any clinical features or co‐morbidities.